TRANSLANGUAGING IN BILINGUAL CLASSROOM: A CASE STUDY OF MATHEMATICS BILINGUAL PROGRAM AT UNIVERSITAS NEGERI MAKASSAR - Hajrah, Hajrah; Sunra, La; Sakkir, Geminastiti (JTechLP: Journal of Technology in Language Pedagogy, 2023)
This research aims to investigate translanguaging in a bilingual classroom. Hence, this research tries to see the practice of translanguaging in bilingual classrooms. This research focused on how translanguaging facilitates the teaching and learning of the Mathematic Bilingual program at Universitas Negeri Makassar. This research applied a qualitative method, and the instruments were classroom observation and interview. The result of observation and interview was transcribed and analyzed based on the research focus. The findings of this research showed that the lecturers expressed a positive perception toward translanguaging which was reflected through ten positive comments about the use of translanguaging in the bilingual classroom. Translanguaging facilitated the teaching and learning of the Mathematic bilingual program was the first to make their English teaching in the classroom effective and the second was to make the students understand the teaching and learning material well. The way lecturers conducted translanguaging was based on the situation of the students. If the students did not understand what the lecturers explained in English, they used translanguaging in the classroom to make the teaching and learning process understandable.